Mapping of the bs5 and bs6 non-race-specific recessive resistances against bacterial spot of pepper - Sharma, Anuj; Li, Jian; Wente, Rebecca; Minsavage, Gerald V.; Gill, Upinder S.; Ortega, Arturo; Vallejos, C. Eduardo; Hart, John P.; Staskawicz, Brian J.; Mazourek, Michael R.; Stall, Robert E.; Jones, Jeffrey B.; et al. (Frontiers in Plant Science, 2023)
Bacterial spot caused by Xanthomonas euvesicatoria is a major disease of pepper (Capsicum annuum L.) in warm and humid production environments. Use of genetically resistant cultivars is an effective approach to manage bacterial spot. Two recessive resistance genes, bs5 and bs6, confer non-race-specific resistance against bacterial spot. The objective of our study was to map these two loci in the pepper genome. We used a genotyping-by-sequencing approach to initially map the position of the two resistances. Segregating populations for bs5 and bs6 were developed by crossing susceptible Early CalWonder (ECW) with near-isogenic lines ECW50R (bs5 introgression) or ECW60R (bs6 introgression). Following fine-mapping, bs5 was delimited to a 535 Kbp interval on chromosome 3, and bs6 to a 666 Kbp interval in chromosome 6. We identified 14 and 8 candidate resistance genes for bs5 and bs6, respectively, based on predicted protein coding polymorphisms between ECW and the corresponding resistant parent. This research enhances marker-assisted selection of bs5 and bs6 in breeding programs and is a crucial step towards elucidating the molecular mechanisms underlying the resistances.